Demain tous cyborgs ? - Jean-Claude Heudin (Territoire en Mouvement)
This article discusses the often evoked hypothesis that the future evolution of human beings will be toward cyborgs. A cyborg, or Cybernetic Organism, is a hybrid creature consisting of organic and cybernetic parts. We argue that in contrast with the vision of a sort of robot consisting of a metal endoskeleton covered with living tissue, the post-human will be a human like us, but probably "enhanced" thanks to advances in the fields of cybertechnology, biotechnology and nanotechnology. Also, devices that will enable a continuous connection to information networks will not be implanted within the body, but rather embedded in clothing near the body.